Fatores determinantes da modernização agrícola na região sul do Brasil - Galle, Vitor (2021)
Over the years, Brazilian agricultural production has grown and stood out nationally and internationally due to technological advances and global demand for food. Brazilian agribusiness is one of the main players and agro-industrial producers in the world, besides it is one of the largest exporters of soy, orange, beef, pork and poultry. Its production and exports generate jobs, income and development apart from representing a large share of the Gross Domestic Product - GDP, generating balance in the Brazilian trade balance. Factors such as climate, relief, soil, rainfall, labor, technology employed and promoting public policies for production make Brazil one of the main food producers in the world. In order to identify the conditioning factors of agricultural modernization in the municipalities of the States of Rio Grande do Sul, Santa Catarina and Paraná, the factor analysis technique was used to calculate the Agricultural Modernization Index (AMI) so as to hierarchize the municipalities of the three States of the southern region of Brazil in terms of agricultural modernization. Then, Exploratory Spatial Data Analysis (ESDA) was applied to analyze how spatial distribution occurs in relation to the intensity of the modernization of agriculture in the three States of the southern region. The main contribution of the study focuses on answering whether there has been agricultural modernization in the southern Brazilian region over the years and, more specifically, in the last agricultural census in 2006 and 2017. This investigation is supported by previous studies on this theme and covers the entire southern region of the country, given its economic, productive and agricultural potential. Main results obtained show that the municipalities that obtained a high index of agricultural modernization are located in the northwestern and eastern center mesoregions of Rio Grande do Sul, in the Vale do Itajaí and west of Santa Catarina and west, central north and metropolitan mesoregions of Paraná. These regions concentrate several of the main agricultural producers of soy, corn, rice, wheat, cultivation of vines and horticultural, orchard and farm products besides allocating large cities with industrial development for agribusiness. Thus, through the Exploratory Spatial Data Analysis (ESDA), it was possible to corroborate the hypothesis that the spatial distribution of the modernization of agriculture is not random due to the positive correlation of the AMI. In this sense, through the analysis of LISA cluster maps, two different types of well-defined clusters were identified for 2006 and 2017. The first well-defined was of the high-high type (HH) and the second of the low-low type (LL). Finally, it can be said that in a certain way, there is a relativity in the Agricultural Modernization Index, because there is a contrast between the most developed regions in relation to the least developed ones, so generalizing that the municipalities are really technologically developed is imprecise.